PREDICTION OF SARDINE FISHING GROUND AS DETERMINED BY MULTI-SENSOR REMOTE SENSING AND GIS - Katsuya Saitoh; Sei-Ichi Saitoh (BRIN, 2008)
Fishing ground predictione analyzed the fishing ground environment of sardines with the complex method combining multi-sensor remote sensing and Geographical Information System (GIS), and examined methods f is now one of the keywords for a planned and efficient use of fishery resources. In this paper, wor prediction. As a result, the study showed the field area of fishing ground formation, the depth of fishing grounds, the favorable environment through time analysis before and after fishing ground formation. Also the study overlaid these results using GIS and showed prediction fishing grounds map.